(untitled) (Global Conference on Medical and Health Sciences, 2026)
Iodine deficiency remains a significant hygienic and epidemiological problem in global health, serving as a primary etiological factor in the development of thyroid disorders, particularly endemic goiter. According to the World Health Organization, approximately 30% of the world’s population is at risk of iodine deficiency.